Adsorption technology and design - Thomas, W. J. (Butterworth-Heinemann, 1998)
Adsorption is of considerable industrial importance and is a major part of many different processes throughout the chemical and process industries, including many reactions - chemical and bio-chemical, purification and filtration, gas and liquid processing and catalysis. Adsorption is a complex process and this makes the correct design and implementation of its operation all the more critical. The aim of this book is to provide all those involved in designing and running adsorption processes with a straightforward guide to the essentials of adsorption technology and design. It will therefore be an important addition to the bookshelves of both student and professional chemical, plant and process engineers in industries as varied as the petrochemical, pharmaceutical and food processing fields. Adsorption is of considerable industrial importance and is a major part of many different processes throughout the chemical and process industries, including many reactions - chemical and bio-chemical, purification and filtration, gas and liquid processing and catalysis. Adsorption is a complex process and this makes the correct design and implementation of its operation all the more critical. The aim of this book is to provide all those involved in designing and running adsorption processes with a straightforward guide to the essentials of adsorption technology and design. It will therefore be an important addition to the bookshelves of both student and professional chemical, plant and process engineers in industries as varied as the petrochemical, pharmaceutical and food processing fields. This book is practically based - other books are research level monographs This is about the basic design and implementation of an important industrial process Written as a straightforward and concise guide.